Cascading training the trainers in ophthalmology across Eastern, Central and Southern Africa - Melanie C Corbett; Wanjiku Mathenge; Marcia Zondervan; Nick Astbury (BMC, 2017)
Abstract Background The Royal College of Ophthalmologists (RCOphth) and the College of Ophthalmology of Eastern Central and Southern Africa (COECSA) are collaborating to cascade a Training the Trainers (TTT) Programme across the COECSA Region. Within the VISION 2020 Links Programme, it aims to develop a skilled motivated workforce who can deliver high quality eye care. It will train a lead, faculty member and facilitator in 8 countries, who can cascade the programme to local trainers. Methods In phase 1 (2013/14) two 3-day courses were run for 16/17 selected delegates, by 3 UK Faculty. In phase 2 (2015/16) 1 UK Faculty Member ran 3 shorter courses, associated with COECSA events (Congress and Examination). A COECSA Lead was appointed after the first course, and selected delegates were promoted as Facilitators then Faculty Members on successive courses. They were given appropriate materials, preparation, training and mentoring. Results In 4 years the programme has trained 87 delegates, including 1 COECSA Lead, 4 Faculty Members and 7 Facilitators. Delegate feedback on the course was very good and Faculty were impressed with the progress made by delegates. A questionnaire completed by delegates after 6-42 months demonstrated how successfully they were implementing new skills in teaching and supervision. The impact was assessed using the number of eye-care workers that delegates had trained, and the number of patients seen by those workers each year. The figures suggested that approaching 1 million patients per year were treated by eye-care workers who had benefited from training delivered by those who had been on the courses. Development of the Programme in Africa initially followed the UK model, but the need to address more extensive challenges overseas, stimulated new ideas for the UK courses. Conclusions The Programme has developed a pyramid of trainers capable of cascading knowledge, skills and teaching in training with RCOphth support. The third phase will extend the number of facilitators and faculty, develop on-line preparatory and teaching materials, and design training processes and tools for its assessment. The final phase will see local cascade of the TTT Programme in all 8 countries, and sustainability as UK support is withdrawn.